Timing protein intake increases energy expenditure 24 h after resistance training - Hackney, K. J.; Bruenger, A. J.; Lemer, J. T. (Medicine & Science in Sports & Exercise, 2010)
Purpose: To determine whether protein supplementation (PRO) before an acute bout of heavy resistance training (HRT) would influence postexercise resting energy expenditure (REE) and the nonprotein respiratory exchange ratio (RER).